THE PROCESS OF LEGAL DRAFTING REGULATION IN THE DEVELOPMENT OF THE NUCLEAR POWER PLANT IN INDONESIA - Amil Mardha (Jurnal Pengembangan Energi Nuklir, 2009)
ABSTRACTTHE PROCESS OF LEGAL DRAFTING REGULATION IN THE DEVELOPMENT OF THE NUCLEAR POWER PLANT IN INDONESIA. In Indonesia, the process of legal drafting to establish the regulation is based on the Act No. 10 Year 2004 on the Establishment of Legislation. The process shall comply with the constitutional and institutional requirements of national political and legal system. In drafting the development of the regulation of nuclear energy, BAPETEN has been involving some other agencies or other related government agencies, and stakeholders such as utility, academic institutions, and publics. In general, in the process of legal drafting, international publications or other country regulations can be a reference and adopted. In the establishment of the regulations of nuclear energy, BAPETEN has issued some Government Regulations and Chairman Regulations of BAPETEN. For nuclear safety of NPP, the regulations have not been completed yet, but some regulations related in the area of siting of NPP have been already available. In this paper, it is discussed the process of the establishment of legislation and of the legal drafting nuclear regulation of NPP, and the current status of NPP regulations.Keywords: regulation, legislation, establishment, legal drafting ABSTRAKPROSES PENYUSUNAN PERATURAN DALAM PEMBANGUNAN PLTN DI INDONESIA. Proses penyusunan pembentukan peraturan perundang-undangan di Indonesia mengacu pada Undang-Undang Nomor 10 Tahun 2004 tentang Pembentukan Peraturan Perundang-undangan dan dalam penyusunannya selain mengikuti UU pembentukan peraturan perundang-undangan juga harus memperhatikan persyaratan-persyaratan konstitusi dan institusi lainnya secara sistem legal dan politis. Dalam menyusun pengembangan peraturan ketenaganukliran, BAPETEN tidak bekerja sendiri namun melibatkan beberapa lembaga/badan pemerintah/swasta dan pemangku kepentingan seperti pengguna, universitas/lembaga akademik dan lembaga lainnya yang relevan/terkait. Pada umumnya, proses pembentukan peraturan perundangan ketenaganukliran dilakukan dengan pendekatan mengadopsi peraturan internasional atau peraturan negara-negara lain yang pantas untuk diacu. BAPETEN telah menerbitkan beberapa peraturan pemerintah dan peraturan kepala BAPETEN mengenai keselamatan ketenaganukliran. Untuk peraturan keselamatan PLTN, memang belum lengkap, namun peraturan PLTN yang terkait dengan tapak telah banyak diundangkan oleh BAPETEN.Kata kunci: peraturan, perundang-undangan, pembentukan, penyusunan peraturan